2021
DOI: 10.1128/aac.01445-20
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of ethA and katG in Mycobacterium marinum Enables the Rapid Identification of New Prodrugs Active against Mycobacterium tuberculosis

Abstract: Screening strategies for anti-tuberculosis compounds using Mycobacterium tuberculosis are time-consuming and require BSL-3 facilities, which makes the development of high-throughput assays difficult and expensive. Mycobacterium marinum, a close genetic relative of M. tuberculosis, possesses several advantages as a suitable model for tuberculosis drug screening. However, despite the high genetic similarity, there are some obvious differences in susceptibility to some tuberculosis drugs between these two species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…After the setup of the in vivo screening approach, the platform was used to screen compounds from an anti-Mtb hit library [provided by TB Alliance (TBA)] for their in vivo activity. This library comprises 1392 compounds previously shown to inhibit Mtb viability in vitro ( Ho et al, 2021 ) . All compounds that showed ≥80% inhibition of M. marinum viability in vitro at 10 µM (240 compounds) were selected and tested further in the zebrafish- M. marinum infection model via automated yolk injection and waterborne treatment using a single dose (10 µM) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the setup of the in vivo screening approach, the platform was used to screen compounds from an anti-Mtb hit library [provided by TB Alliance (TBA)] for their in vivo activity. This library comprises 1392 compounds previously shown to inhibit Mtb viability in vitro ( Ho et al, 2021 ) . All compounds that showed ≥80% inhibition of M. marinum viability in vitro at 10 µM (240 compounds) were selected and tested further in the zebrafish- M. marinum infection model via automated yolk injection and waterborne treatment using a single dose (10 µM) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, zebrafish embryos were used to evaluate the efficacy and toxicity of several anti-TB drugs ( Ho et al, 2021 ; Makarov et al, 2014 ; Ordas et al, 2015 ), including PBTZ169 (macozinone), which is currently in phase 2 of a clinical trial. The M. marinum -zebrafish model can be established by injecting bacteria via the caudal vein or by injection in the yolk.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have employed varying numbers of embryos per experimental group. For instance, studies using a single bacterial strain with different compound treatments have utilized 5–10 embryos per treatment group (Ho et al 2021 , Winters et al 2022 ), 12–15 embryos (Habjan et al 2021 , Schouten et al 2022 ), as well as 20–30 (Ordas et al 2015 , Dalton et al 2017 , Goh et al 2023 ) or even more than 30 zebrafish embryos per experimental group (Wambaugh et al 2017 ). The optimal number may vary depending on experimental requirements and constraints.…”
Section: Administration Routes Of Infecting Bacterial Pathogen In Zeb...mentioning
confidence: 99%
“…Besides showing the activity of known antibiotics like delamanid, pretonamid, and rifampicin, they also showed the activity of two novel pretonamid analogues SN30527 and SN30488. Another study described several zebrafish-active prodrugs (Ho et al 2021 ), which were identified by using the M. marinum strain overexpressing katG and ethA , two common prodrug-activating enzymes. Furthermore, the efficacy of several nitronaphthofuran derivatives was investigated in a zebrafish– M. marinum model, where compounds were injected into the zebrafish posterior cardinal vein, which is the vein that follows the upper side of the yolk extension and leads to the caudal vein (Thisse et al 2001 ).…”
Section: Evaluation Of Antibacterial Compounds In Zebrafish Embryo In...mentioning
confidence: 99%
See 1 more Smart Citation